Understanding the gap between guidelines and influenza vaccination coverage in people with diabetes: a scoping review - Brice Mastrovito; Alexia Lardon; Amelie Dubromel; Viviane Nave; Karen Beny; Claude Dussart; Claude Dussart (Frontiers Media S.A., 2024)
BackgroundDiabetes affects millions of people worldwide, making them more vulnerable to infections, including seasonal influenza. It is therefore particularly important for those suffering from diabetes to be vaccinated against influenza each year. However, influenza vaccination coverage remains low in this population. This review primarily aims to identify the determinants of influenza vaccination in people with diabetes (T1D or T2D). Secondly, it aims to assess main recommendations for influenza vaccination, vaccine effectiveness, vaccination coverage, and how education and pharmacists can encourage uptake of the vaccine in the diabetic population.MethodsA scoping review was conducted in January 2022 to systematically review evidence on influenza vaccination in people with diabetes using data from PubMed, Science Direct, and EM Premium with terms such as "Diabetes mellitus," "Immunization Programs," "Vaccination," and "Influenza Vaccines." Quality assessment and data extraction were independently conducted by two authors. Disagreements between the authors were resolved through discussion and consensus, and if necessary, by consulting a third author.ResultsOf the 333 records identified, 55 studies met the eligibility criteria for inclusion in this review. Influenza vaccination was recommended for people ≥6 months. Despite effectiveness evidence showing a reduction in mortality and hospitalizations in people with diabetes vaccinated vs. non-vaccinated ones, very few studies reported a coverage rate ≥ 75%, which is WHO's target objective. Determinants such as advanced age, presence of comorbidities and healthcare givers' advice were associated with increased vaccination uptake. On the contrary, fear of adverse reactions and concerns about vaccine effectiveness were significant barriers. Finally, education and pharmacists' intervention played a key role in promoting vaccination and increasing vaccination uptake.ConclusionInfluenza vaccination coverage in people with diabetes remains low despite recommendations and evidence on vaccine effectiveness. Motivators and barriers as well as several socio-demographic and clinical factors have been identified to explain this trend. Efforts are now needed to increase the number of diabetics vaccinated against influenza, mainly through education and the involvement of healthcare givers.